Managing touristic destinations: content analysis on language of promotion in gililife magazine, Indonesia - Ramli, Muhammad; Malik, Abdul; Basri, Hasan (Enrichment : Journal of Management, 2023)
The research discusses marketing promotion in the context of language use in promoting destinations. This scientifically answers the research question formulated on the promotional linguistic content used in discourses of Gililife magazine within one published edition. Discourse analysis as a method of analysis was employed under the descriptive-qualitative approach. Four steps were utilized to analyze the data deeply: collecting, reducing, displaying data, and drawing a conclusion. The data source was the selection of two discourses only discussing destinations with four tourism components (attraction, amenity, accessibility, security) as a basis for content analysis. Findings show that analyzed discourses dominantly emphasized marketing promotion on attraction and amenity. However, security is being neglected in every single discourse. Language content applied is the denotative preference, although few metaphor words are included.